The Confederation of Canadian Unions (CCU), 1969-1992 - Godden, Mason (My University, 2024)
This dissertation provides the first historical overview of the Confederation of Canadian Unions (CCU) and its affiliates from 1969 to 1992. Formed at the end of the 1960s as a foil to the Canadian Labour Congress (CLC), the CCU sought to nationalize the Canadian labour movement by fomenting the formation of Canadian unions. As a left-nationalist labour body, the CCU charged the CLC with conservatism, complacency, and collaboration in its approach to organizing and collective bargaining. Chief among the CCU’s concerns was the domination of American international unions in the CLC. Throughout the 1970s and 1980s, the CCU organized workplaces in unorganized industries, bringing a host of immigrant women into the ranks of the Canadian labour movement, while establishing large bargaining units in industries primarily organized by American unions. At the same time, the CCU forwarded a left-nationalist politics inspired by the New Canadian Political Economy (NCPE) that criticized Canada’s economic, political, and cultural dependence on the United States, and used this politics to mobilize its members against continental free trade and towards a nationalized, socialized home economy. The CCU and its affiliates also formed important linkages with the New Left and the women’s movement during these decades and proved itself a militant actor in confrontations with the state and industrial law. Several CCU affiliates eventually merged with the Canadian Autoworkers (CAW) in the 1990s in the wake of extensive economic restructuring and corresponding changes in the Canadian labour movement. The dissertation contributes to the scholarship on industrial relations, industrial legality, and nationalism by providing a historical case study of a left-nationalist labour institution that simultaneously challenged and was shaped by federal and provincial law. It provides a critical institutionalist perspective on union federations that accounts for the law as a contested terrain, and nationalism as a historically contingent politics.
Keywords: labour; history; Canada; union; unions; industrial relations; industrial legality; nationalism; left-nationalism; the left; union federations; labour institution; labour institutions; institutional history; critical institutionalism; women's movement; feminism; work; employment